FAKTOR – FAKTOR YANG MEMPENGARUHI KUALITAS HASIL AUDIT - Renya Rosari (Wahana: Jurnal Ekonomi, Manajemen dan Akuntansi, 2017)
The purpose of this research is to empirically investigate the influence of independence, experience, responsive, proffesional care, audit planning and executive involment on quality of audit result on BPKP of East Nusa Tenggara province goverment’s. The research as explanatory research. The survey method data collecting of East Nusa Tenggara Province goverment’s on method was the approach that was used in this research. The population is BPKP of the East Nusa Tenggara Province. There were 73 questionnaire distributed and 73 questionnaire returned and internal auditor as the sample that used in the research. The technique analysis used Multiple regression using IBM SPSS 23 software. The test was done by validity test, realibility test, assumption classic test and hypothesis test. The result of the research found that among the six independen variables, (that were independence, experience, responsive, proffesional care, audit planning and executive involment) showed that three independen variabel had effect on quality audit result is experience, proffesional care, and executive involment. Keyword : quality audit result, independence, experience, responsive, proffesional care, audit and executive involment